2016
DOI: 10.3390/ijerph13090914
|View full text |Cite
|
Sign up to set email alerts
|

Do They Need Goals or Support? A Report from a Goal-Setting Intervention Using Physical Activity Monitors in Youth

Abstract: The objective of this study was to investigate the association between physical activity (PA) and different goal setting and strategies in youth. The study took into consideration different sources of support as well as gender variations. Classmate and Teacher Support scales were used to evaluate support in physical education (PE) classes, and moderate-to-vigorous physical activity (MVPA) was reported. Garmin Vivofit® activity trackers were used during an 8 week-long intervention to count daily steps. Data was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 49 publications
5
37
0
3
Order By: Relevance
“…Overall, a possible explanation of those correlations could be the nature of the physical education's core curriculum, which may reflect the type and variety of activities typically undertaken by adolescents in classes conducted separately for girls and boys. Similar trends were observed in an earlier study on Polish adolescents [3], where it was also found that for the long-term effects of school-based physical activity young people need to develop a sense of coherence and self-responsibility. Also, Kantanista et al [14] found a correlation between effectiveness of school-based interventions increasing the volume of activities (including in out-of-school leisure time) and biological and psychological characteristics of Polish adolescents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, a possible explanation of those correlations could be the nature of the physical education's core curriculum, which may reflect the type and variety of activities typically undertaken by adolescents in classes conducted separately for girls and boys. Similar trends were observed in an earlier study on Polish adolescents [3], where it was also found that for the long-term effects of school-based physical activity young people need to develop a sense of coherence and self-responsibility. Also, Kantanista et al [14] found a correlation between effectiveness of school-based interventions increasing the volume of activities (including in out-of-school leisure time) and biological and psychological characteristics of Polish adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Data for this study were obtained from the "Active not only online" project supported by a Grant Study, Akademickie Centrum Kreatywności (Academic Center of Creativity, no MNiSW/2014/DIR/612/ACK) by the Polish Ministry of Science and Higher Education, that was started in 2015 to conduct a goal setting intervention using PA monitors in youth residing in the city of Poznan in Poland. More information on the setting and study design has been provided elsewhere [3].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Scholars have studied the issue in the general educational setting and how this interferes with the effectiveness of sport education [25], as well as in physical activity (PA) contexts [40,22]. The findings are equivocal -some studies suggest that PA and pro-social behaviour in pupils improves as a result of engagement in PE and sport [8], even more so when receiving support from PE teachers [9], while in some circumstances behaviour actually worsens [4]. Bailey et al [3] claim that school PE and sport has the potential to contribute to the whole development of young people in 4 domains -physical, social, affective and cognitive -though in the case of social and cognitive effects benefits are mediated by environmental and contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this small study, they successfully increased MVPA by 25% from baseline [ 19 ]. To our knowledge, only one other study has used physical activity monitors in the context of a school-based physical activity intervention [ 20 ]. Whereas the study was well executed, it was designed to evaluate how different types of activity goals affect achievement and whether peer or teacher support mediates activity behaviors.…”
Section: Introductionmentioning
confidence: 99%